Exploring the Potential of Laser Ablation for Multi-functional Nanoparticle Production - Kaushki Kanna; Darshpreet Singh; Usha Shukla (International Journal of Radio Frequency Innovations, 2024)
The extraordinary class of materials known as nanomaterials has come into being. A large variety of elements with minimum one dimension between 1 and 100 nm are included. Reasonably designed nanomaterials can have exceptionally large surface areas. Nanomaterials can be made to have exceptional mechanical, optical, electrical, magnetic, and catalytic properties that are very different from those of their bulk counterparts. To achieve the necessary features tuning, nanomaterials' size, shape, synthesis conditions, and proper functionalisation can all be precisely controlled. One technique for creating several types of nanoparticles is laser ablation. These include core shell nanoparticles, semiconductor quantum dots, carbon nanotubes, and nanowires. Using this technique, species that have been laser-vaporized in a background gas nucleate and proliferate to form nanoparticles. By rapidly quenching vapour, high purity nanoparticles across the quantum size range (< 10 nm) can be produced. This paper reports the laser ablation method's benefits, including precise material removal, minimal heat damage, and applicability across various fields, highlight its potential as a key tool in nanoparticle synthesis and material processing.
Keywords: Laser ablation method; benefits; material processing; nanoparticle synthesis